PENGARUH PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP CITRA PERUSAHAAN PT SEMEN PADANG - Muhammad Gozaly; Dion Eriend (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is entitled “The Influence of the Corporate Social Responsibility (CSR) Program on the Corporate Image of PT Semen Padang” In carrying out its operational activities, a company is not only profit-oriented but also has responsibilities toward the surrounding community and environment. Corporate Social Responsibility (CSR) is one of the company’s efforts to build and maintain a positive corporate image. This study aims to explain the influence of the Corporate Social Responsibility (CSR) Program in terms of social, economic, and environmental aspects on corporate image. This research uses an associative quantitative method with a total sample of 100 respondents, who are residents of Pauh District, Padang City, selected using a purposive sampling technique. Data analysis was conducted using multiple linear regression with IBM SPSS version 26. The results show that the social and environmental aspects have a positive and significant effect on corporate image, while the economic aspect has a positive but not significant effect. Simultaneously, the three CSR aspects have a significant effect on corporate image, with a coefficient of determination value of 59.3%.